2013
DOI: 10.4103/2230-8229.114769
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and its associated factors among primary school children in suburban Selangor, Malaysia: A cross-sectional survey

Abstract: Background:Little is known about the relationship of blood pressure (BP) with adiposity indicators, dietary habits, physical activity, and sleep in school children in Malaysia. We aimed to study about the distribution of BP and its associated factors in primary school children.Materials and Methods:A survey was carried out on a random sample of 335 children in five primary schools. BP was measured with a mercury sphygmomanometer. Anthropometry was done by standard methods. Demographic information, dietary habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
(86 reference statements)
3
12
1
Order By: Relevance
“…the prevalence of prehypertension and hypertension in this study, it was found to be 13.5% and 8.1%, respectively, lower than other local studies (pre-hypertension 12.23%, hypertension 13-14%) (Screeamareddy et al 2013;, the prevalence of overweight and obesity (36.9%), overfat and obese (31.0%), abnormal waist circumference (29.0%) and waist-toheight ratio (32.8%) was high among the respondents. Literature reported that obesity itself can be the main factor that is strongly associated with hypertension, carried a relative risk of 14.7 for systolic hypertension after adjustment for family history (Salman et al 2011).…”
Section: Despitecontrasting
confidence: 81%
See 3 more Smart Citations
“…the prevalence of prehypertension and hypertension in this study, it was found to be 13.5% and 8.1%, respectively, lower than other local studies (pre-hypertension 12.23%, hypertension 13-14%) (Screeamareddy et al 2013;, the prevalence of overweight and obesity (36.9%), overfat and obese (31.0%), abnormal waist circumference (29.0%) and waist-toheight ratio (32.8%) was high among the respondents. Literature reported that obesity itself can be the main factor that is strongly associated with hypertension, carried a relative risk of 14.7 for systolic hypertension after adjustment for family history (Salman et al 2011).…”
Section: Despitecontrasting
confidence: 81%
“…A recent school survey carried out locally indicated that 12.23% of the children were prehypertensive and 13.4% hypertensive. The mean systolic blood pressure and diastolic blood pressure were higher among those children who were overweight and obese (Screeamareddy et al 2013).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Screening of school children for BP has identified obesity and family history of diabetes mellitus, ischemic heart disease and hypertension as significant risk factors 11,13,15 . Amongst the adiposity indicators body mass index (BMI) and waist circumference seems (WC) to be positively associated with increasing BP [16][17][18] . The risk for elevated BP in children is three times greater in obese children compared to non-obese children 19 .…”
Section: Introductionmentioning
confidence: 99%